2015
DOI: 10.1097/qai.0000000000000489
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Age on Retention in Care and Viral Suppression

Abstract: Background Retention in care is important for all HIV-infected persons and is strongly associated with initiation of antiretroviral therapy and viral suppression. However, it is unclear how retention in care and age interact to effect viral suppression. We evaluated whether the association between retention and viral suppression differed by age at entry into care. Methods Cross-sectional analysis (2006-2010) involving 17,044 HIV-infected adults in 14 clinical cohorts across the U.S. and Canada. Patients cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
64
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 42 publications
11
64
1
2
Order By: Relevance
“…Retention in care and HIV disparities research have been linked through numerous studies describing the relationship between clinical engagement, access to and initiation of therapy, continuity of care, and viral suppression and other markers of HIV disease progression in various populations and settings, both in resource-rich and resource-limited settings. 12,13,15,16,18,[29][30][31] In fact, the relationship between retention disparities and lack of viral suppression alone merits close attention as viral suppression is a priority outcome in the NHAS, implicating improved individual outcomes and reduced HIV transmission. 5,8,[29][30][31] Few studies, however, have followed a cohort as large as the NA-ACCORD population over such a long period of time after ART initiation, a long enough period to directly observe the median times of first discontinuity of retention in care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Retention in care and HIV disparities research have been linked through numerous studies describing the relationship between clinical engagement, access to and initiation of therapy, continuity of care, and viral suppression and other markers of HIV disease progression in various populations and settings, both in resource-rich and resource-limited settings. 12,13,15,16,18,[29][30][31] In fact, the relationship between retention disparities and lack of viral suppression alone merits close attention as viral suppression is a priority outcome in the NHAS, implicating improved individual outcomes and reduced HIV transmission. 5,8,[29][30][31] Few studies, however, have followed a cohort as large as the NA-ACCORD population over such a long period of time after ART initiation, a long enough period to directly observe the median times of first discontinuity of retention in care.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 This retention measure has also been noted to correlate strongly with several other metrics and to be independently associated with negative clinical outcomes such as lack of viral suppression. 1,5,[29][30][31] This retention definition was anchored to calendar time to create estimates comparable with other studies and cliniclevel reports applying the indicator in regular reporting intervals. Disruption of continuous retention (discontinuity) was defined as the first instance of failing to meet the IOM indicator definition in any calendar year after ART initiation and before study follow-up ended.…”
Section: Inclusion Criteria and Variables Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…8,[26][27][28][29] Prior studies have shown the strong correlation between retention and viral load suppression. [30][31][32] With the notable disparities in outcomes and poor viral load suppression rates among youth, the importance of retaining young people in care is critical. Determining the structures of care available in HIV clinic settings that support retention in care for this challenging population can facilitate a greater number of youth to initiate ART earlier and ultimately achieve viral load suppression.…”
Section: Discussionmentioning
confidence: 99%
“…To fully benefit from cART, it is essential that HIV-infected persons successfully engage in all steps along the continuum of care [1].…”
Section: Introductionmentioning
confidence: 99%